High-Level Fosfomycin Resistance in Vancomycin-Resistant Enterococcus faecium - Guo, Yan (Emerg Infect Dis, 2017)
Of 890 vancomycin-resistant Enterococcus faecium isolates obtained by rectal screening from patients in Pittsburgh, Pennsylvania, USA, 4 had MICs >1,024 μg/mL for fosfomycin. These isolates had a Cys119Asp substitution in the active site of UDP-N-acetylglucosamine enolpyruvyl transferase. This substitution increased the fosfomycin MIC >4-fold and rendered this drug inactive in biochemical assays.